2010
DOI: 10.14221/ajte.2010v35n8.4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between University Students’ Chemistry Laboratory Anxiety, Attitudes, and Self-Efficacy Beliefs

Abstract: The aim of this study is to examine the relationships between chemistry laboratory anxiety, chemistry attitudes, and self-efficacy. Participants were 395 university students. Participants completed the Chemistry Laboratory Anxiety Scale, the Chemistry Attitudes Scale, and the Self-efficacy Scale. Results showed that chemistry laboratory anxiety was correlated negatively to chemistry attitudes and to self-efficacy. On the other hand, chemistry attitudes were found to be positively associated with self-efficacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 57 publications
10
82
0
15
Order By: Relevance
“…The similar finding aligns with previous studies. For example, Kurbanoglu and Akim (2010) found that the chemical experiments were influencing the pupils' attitudes toward chemistry in positive way. It seems, the chemical experiments and adequate using of chemical aids could influence pupils' perceptions of chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The similar finding aligns with previous studies. For example, Kurbanoglu and Akim (2010) found that the chemical experiments were influencing the pupils' attitudes toward chemistry in positive way. It seems, the chemical experiments and adequate using of chemical aids could influence pupils' perceptions of chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Students' hesitancy in answering the questions was caused by the limited confidence in dealing with the answers given. Kurbanoglu & Akin (2010) reported that students who fully understand a concept will have high confidence. From this statement, it can be interpreted that the students who answer the question with a lower CRI value (1-2) lack concept understanding.…”
Section: Methodsmentioning
confidence: 99%
“…Mostly, students understand concept but not confident whit their answers, show the adding reasoning in every students' answer will help to analyze data. According to Kurbanoglu et al [18], students who master the concept well also have high confidence.The modification of CRI scaling was also performed as recommended by Potgieter et al [19], by using four scales (1-4), 1 = guessing, 2 = not certain, 3 = certain, 4 = very certain.…”
Section: Experimental Methodsmentioning
confidence: 99%